Great culture of the Great War - V. N. Leksin (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2015)
Soviet culture of that time was plethoric and rich: imaganative literature was published in huge numbers (including children), masterpieces of popular songs and classical music were created, documentaries and feature films were released, stage didn't cease and so on. The best poets and writers created, snitzy actors and musicians took part in the front-line teams, thousands of journalists and photographers came voluntarily in the front-line newspapers. It didn't happen in the world history.